Spiritualty in Modern Art - Rulofson, Chelsea Ann (My University, 2010)
This thesis includes the interpretation of art as a religious device in early history that was essentially, exclusively used within the context of spirituality. Art from around the world reveals the deep roots between spirituality and art. Looking then to modern times, the influence of Darwinian Theory and science on artists at the time divulges a different type of spirituality that does not need any God, gods, spirits, or ancestors for creation or for art. Philosophies of humanism and cosmic humanism begin to take the spiritual stage in art. Art and its relationship with spirituality and with people in most cases no longer serves a communal purpose and has become a tool of the individual's inner expression, which excludes instead of includes people. The transition has been from artists making art that was for the pleasure of a deity to artists transforming, philosophically, into their own deity and making art to please themselves alone. Through this research into art and spirituality, the relevance of modern art is examined.
Keywords: science; Darwinian Theory; spirituality; religious device; art; Visual Arts; Art History